Reconstructing Macroevolutionary Patterns in Avian MHC Architecture With Genomic Data - He, Ke; Liang, Chun-hong; Zhu, Ying; Dunn, Peter; Zhao, Ayong; Minias, Piotr (Frontiers in Genetics, 2022)
The Major Histocompatibility Complex (MHC) is a hyper-polymorphic genomic region, which forms a part of vertebrate adaptive immune system and is crucial for intra- and extra-cellular pathogen recognition (MHC-I and MHC-IIA/B, respectively). Although recent advancements in high-throughput sequencing methods sparked research on the MHC in non-model species, the evolutionary history of MHC gene structure is still poorly understood in birds. Here, to explore macroevolutionary patterns in the avian MHC architecture, we retrieved contigs with antigen-presenting MHC and MHC-related genes from available third-generation sequencing genomes. We identified: 1) an ancestral avian MHC architecture with compact size and tight linkage between MHC-I, MHC-IIA/IIB and MHC-related genes; 2) three major patterns of MHC-IIA/IIB unit organization in different avian lineages; and 3) lineage-specific gene translocation events (e.g. separation of antigen-processing TAP genes from MHC-I region in passerines), and 4) the presence of a single MHC-IIA gene copy in most taxa, showing evidence of strong purifying selection (low dN/dS ratio and low number of positively selected sites). Our study reveals long-term macroevolutionary patterns in the avian MHC architecture and provides the first evidence of important transitions in the genomic arrangement of MHC region over the last 100 million years of bird evolution.